Oral voriconazole monotherapy for fungal keratitis: efficacy, safety, and factors associated with outcomes - Cai, Youran; Song, Shimei; Chen, Yiying; Xu, Xuyang; Zou, Wenjin (Frontiers in Medicine, 2023)
Purpose To provide preliminary data on the efficacy and safety of oral voriconazole (VCZ) as a primary treatment for fungal keratitis (FK). Method We performed a retrospective histopathological analysis of data on 90 patients with FK at The First Affiliated Hospital of Guangxi Medical University between September 2018 and February 2022. We recorded three outcomes: corneal epithelial healing, visual acuity (VA) improvement, and corneal perforation. Independent predictors were identified using univariate analysis, and multivariate logistic regression analysis was used to identify independent predictive factors associated with the three outcomes. The area under the curve was used to evaluate the predictive value of these factors. Results Ninety patients were treated with VCZ tablets as the only antifungal drug. Overall, 71.1% (n = 64) of the patients had extreme corneal epithelial healing, 56.7% (n = 51) showed an improvement in VA, and 14.4% (n = 13) developed perforation during treatment. Non-cured patients were more likely to have large ulcers (≥5 × 5 mm2) and hypopyon. Conclusion The results indicated that oral VCZ monotherapy was successful in the patients with FK in our study. Patients with ulcers larger than 5 × 5 mm2 and hypopyon were less likely to respond to this treatment.